Problematika Implementasi Scientific Approach dalam Pembelajaran Fikih (Studi Kasus Di MTs. PAI Medan) - Rahmat Rifai Lubis; Haidir ,; Bobi Erno Rusadi (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
The implementation of the 2013 curriculum hopes that learning will be carried out actively. One effort to activate student learning is by using a scientific approach. Conceptually, this scientific approach is expected to be effective in creating active and scientific students. But the concept is not in line with the phenomenon of learning practices in the field. Many of the students actually become stiff and have difficulty in following the learning path. This paper aims to find out: (1) Implementation of the scientific approach in Fikih learning in MTS. PAI Medan, (2) Problems in implementing the scientific approach to Fikih lessons in MTS. PAI Medan, (3) Solutions to the problems of the Scientific Approach in Fikih learning in MTS. PAI Medan. The method used in this study is qualitative research with a case study approach. The results showed that the implementation of the scientific approach was carried out through five teaching experiences namely observing, asking, gathering information, associating, and communicating. Problems in implementing the scientific approach First, the unfamiliarity of students in thinking scientifically. Second, student difficulties in reasoning information. Third, lack of learning facilities. Fourth, the lack of learning resources available in the library. Fifth, students lack courage. Sixth, the function of the teacher as a facilitator sometimes does not work. Seventh, students have difficulty communicating the results of their scientific activities. Eighth, the occurrence of knowledge gaps between students. The solution to overcome these problems is to provide additional knowledge through training, and form teacher working groups.